2020
DOI: 10.1177/1932296820967011
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Cost-Effectiveness Modeling of Primary Care-Based, Nonmydriatic Automated Retinal Image Analysis Screening Among Low-Income Patients With Diabetes

Abstract: Background: Artificial intelligence-based technology systems offer an alternative solution for diabetic retinopathy (DR) screening compared with standard, in-office dilated eye examinations. We performed a cost-effectiveness analysis of Automated Retinal Image Analysis System (ARIAS)-based DR screening in a primary care medicine clinic that serves a low-income patient population. Methods: A model-based, cost-effectiveness analysis of two DR screening systems was created utilizing data from a recent study compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…One such study found a cost-savings of 23.3% for diabetic eye screening conducted by automated widefield nFP provided in the primary care setting as compared with standard dilated retinal examinations. 29 However, our model does not consider the additional costs of acquiring the necessary training and equipment (i.e. fundus camera) for teleophthalmology or its maintenance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One such study found a cost-savings of 23.3% for diabetic eye screening conducted by automated widefield nFP provided in the primary care setting as compared with standard dilated retinal examinations. 29 However, our model does not consider the additional costs of acquiring the necessary training and equipment (i.e. fundus camera) for teleophthalmology or its maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they found significantly higher rates of newly-diagnosed DR, compared with the rate in our study. 29,[35][36][37][38][39][40][41] For example, Jani et al 37 found that 20.3% of screened patients had evidence of DR, but those patients lived in rural areas, were mostly non-white, and had not had recent eye examinations. Similarly, Owsley et al 36 found that 21.7% of patients screened positive for DR in a largely uninsured, underserved minority population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations